Deflating Miconia (Melastomataceae) from Eastern Brazil, with 31 new synonyms and other nomenclatural issues - Caddah, Mayara K.; Augustin, Ana Flávia; Goldenberg, Renato (Phytotaxa, 2020)
We propose 31 synonyms for nine South American species of Miconia (Melastomataceae), mostly from the Atlantic Forest in Brazil (with one species in “campos rupestres” and another from the Atlantic Forest in Paraguay); all belong to the ‘Miconia discolor clade’. Of these synonyms, 19 are species and 12 are varieties or subspecies, all of them described by the end of the XIX or early XX centuries, and most of them known in herbaria mostly from isotypes or syntypes (except for Miconia cabucu, M. chartacea and M. saldanhae). Miconia flammea var. major is synonymized under M. brunnea; Miconia amambayensis and M. oblongifolia under M. buddlejoides; Miconia augusti, M. divaricata, M. fasciculata subsp. catharinensis, M. fasciculata var. robusta, M. fluminensis, M. gilva, M. rabenii, M. saldanhae, M. saldanhae var. grandifolia and M. saldanhae var. subsessilifolia under M. fasciculata; Miconia chartacea, M. chartacea var. angustifolia, M. chartacea var. brevifolia, M. chartacea var. longifolia and M. chartacea var. miqueliana sob M. flammea; Miconia altissima, M. cabucu, M. formosa var. angustifolia, M. gigantea, M. mourae, and M. ovalifolia under M. formosa; Miconia ovata under M. organensis; Miconia maximowicziana and M. maximowicziana var. major under M. sclerophylla; Miconia eichleri, M. eichleri var. australis, and M. pseudoeichleri under M. valtheri; and Miconia argyraea under M. willdenowii. We also designate lectotypes for all names but M. fasciculata subsp. catharinensis, M. maximowicziana and M. ovata, which already have holotypes designated by the respective authors. We corrected the spelling of M. buddlejoides (previously known as M. budlejoides), M. saldanhae (formerly M. saldanhaei) and M. mourae (formerly M. mouraei). In the present century, 14 species of Miconia s.s. have been described for the Atlantic Forest, and another 43 species, subspecies and varieties have been synonymized (including the ones performed here). This means that a significant inflation of names has been corrected, since the genus has been deflated by 29 taxa. The synonyms proposed here will help students of the family and other researchers employ the correct names in biological studies, which in turn will help to fine tune biodiversity studies and conservation efforts.